Factors influencing production of hygienic raw milk by small scale dairy producers in selected areas of the Jaffna district, Sri Lanka. - Sukanthy, V.; Sinniah, J.; Nagalingam, K. (Springer, 2009)
The objective of the study was to investigate the influence of dairy cow management techniques and milking methods on hygienic quality of raw milk. Total Bacterial Count (TBC) and Total Coliform Colonies (TCC) were studied to determine the effects. Investigations were carried out in fifty dairy farms from August 2007 to December 2007. The mean TBC and TCC for the herds with comparatively good and poor management practices were 0.9 x 10(5) cfu/ml and 0.2 x 10(3)/ml and 99 x 10(5) cfu/ml and >180 x 10(3)/ml, respectively. The overall mean TBC (22 x 10(5) cfu/ml) and TCC (47 x 10(3)/ml) obtained in this study exceeded the internationally recommended levels for TBC (10(5) cfu/ml) and TCC (<1,000/ml). The overall results obtained suggested that the raw milk tested was of poor hygienic quality with the presence of a great variability among milk samples
Keywords: Raw milk; Hygienic Quality; Dairy microbiology; Total coliform count